2005
DOI: 10.1104/pp.105.059303
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Salicylic Acid in the Induction of Cell Death in Arabidopsis acd11

Abstract: Salicylic acid (SA) is implicated in the induction of programmed cell death (PCD) associated with pathogen defense responses because SA levels increase in response to PCD-inducing infections, and PCD development can be inhibited by expression of salicylate hydroxylase encoded by the bacterial nahG gene. The acd11 mutant of Arabidopsis (Arabidopsis thaliana L. Heynh.) activates PCD and defense responses that are fully suppressed by nahG. To further study the role of SA in PCD induction, we compared phenotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 60 publications
7
107
0
Order By: Relevance
“…1). This function has already been shown for the Arabidopsis ICS1 gene (12,35). Here, we provide the genetic evidence that both ICS1 and ICS2 are also required for the synthesis of PhQ.…”
Section: Essential Role Of Phylloquinone In Higher Plants-the Analysimentioning
confidence: 56%
See 1 more Smart Citation
“…1). This function has already been shown for the Arabidopsis ICS1 gene (12,35). Here, we provide the genetic evidence that both ICS1 and ICS2 are also required for the synthesis of PhQ.…”
Section: Essential Role Of Phylloquinone In Higher Plants-the Analysimentioning
confidence: 56%
“…suggesting that PhQ or its intermediates could trigger cell death responses associated with plant defense against phytopathogens (35). In any case, a metabolic link between photosynthesis and plant resistance has now been established that provokes further investigations.…”
Section: Essential Role Of Phylloquinone In Higher Plants-the Analysimentioning
confidence: 99%
“…These studies have shown that catalase deficiency in tobacco and Arabidopsis mimics many of the effects of environmental stresses on gene expression and on redox homeostasis (Willekens et al, 1997;Chamnongpol et al, 1998;Mittler et al, 1999;Vandenabeele et al, 2004;Vanderauwera et al, 2005;. While many mutants that show spontaneous lesion formation have been described (Dietrich et al, 1994;Lorrain et al, 2003;Brodersen et al, 2005;Meng et al, 2009), questions remain concerning the relationship of the affected genes to changes in ROS availability, which are known to be important in the responses of plants to stress. Unlike many lesion-mimic mutants, increased H 2 O 2 availability is unambiguously the initiating signal of responses in catalase-deficient plants.…”
Section: Discussionmentioning
confidence: 99%
“…In some lesion-mimic mutants, a link with SA has been demonstrated, although in several cases the role of SA itself is less clear (Hunt et al, 1997;Lorrain et al, 2003;Brodersen et al, 2005;Meng et al, 2009). Previous studies showed that SA accumulates in catalase-deficient tobacco (Takahashi et al, 1997;Chamnongpol et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The basal level of SA can vary between species and even within the same plant family (Raskin et al, 1990). For Arabidopsis, basal levels of SA between 2 mmol and 8 mmol g 21 FW have been reported (Brodersen et al, 2005;Klessig et al, 2016;Nawrath and Métraux, 1999;Wildermuth et al, 2001), with SA rising to ;40 mmol g 21 FW during infection, which has been equated to ;70 mM inside infected plant cells (Bi et al, 1995). The importance of SA in response to biotic and abiotic stress and its involvement in the transcriptional regulation of defense genes has been extensively studied and reviewed (Herrera-Vásquez et al, 2015).…”
Section: Low Concentrations Of Sa Increase Sqr Activitymentioning
confidence: 99%